Effect of the system of commercial laying in cages and in floor (Research, Society and Development, 2020)
The objective was to evaluate the effect of breeding laying hens system on performance, egg quality and rectal temperature of birds. One hundred laying hens Hy-Line W-36 and 100 laying hens Hy-Line Brown with 30 weeks of age distributed in a completely randomized design in a factorial 2 x 2, wi five replicates and ten birds each. The performance variables studied were egg with eight, feed intake, feed conversion (kg / kg), feed conversion (kg / dz) and egg production. For quality were analyzed percentage of albumen, yolk percentage, yolk index, Haugh unit, shell thickness and non-commercial eggs. Rectal temperature was assessed at 34; 38; 42 and 46 weeks of age. The results were submitted to analysis of variance and means compared by Tukey test at 5% probability, using the SAS statistical software. The conversion (kg / dz), yolk percentage, yolk index, Haugh unit, percentage of egg production, not commercial eggs percentage did not differ between housing systems. The feed intake, feed conversion (kg / kg), and egg weight were higher for the floor system. Rectal temperature was higher in breeding system in cages. Brown birds had higher yolk percentage, yolk index and Haugh unit. Lightweight birds showed higher percentage albumen, shell thickness. It was concluded that laying hens can achieve satisfactory results when compared to conventional cage rearing system.